Cavalier South vs Puritan North? Hypocrisy and Identity in the American Civil War - Manger, Edward George (Studies in church history, 2024)
During the antebellum period and American Civil War, ‘puritan’ was a contested identity, fraught with layers of meaning and interpretation. Historians have charted the ways Southern intellectuals cast the differences between North and South as an outplaying of the old conflict between Cavalier and puritan. This article highlights the ways Southern ministers claimed the puritan identity for the South and accused the North of hypocrisy, for having fallen far from the theological ideals of their puritan forebears. Furthermore, Southern ministers noted the hypocrisy of Northern puritans for having escaped religious tyranny only to impose it upon those who did not conform to their form of Christianity; they had thus fallen into the very sin which they had decried. This came from Southern ministers whose attempt to appropriate the memory of puritanism as liberty-loving revealed their own hypocrisy in fighting for the ‘liberty’ to maintain a system of racial slavery.